A Mixed-Methods Study of Creative Problem Solving and Psychosocial Safety Climate: Preparing Engineers for the Future of Work - Oppert, Michelle L.; Dollard, Maureen F.; Murugavel, Vignesh R.; Reiter-Palmon, Roni; Reardon, Alexander; Cropley, David H.; O’Keeffe, Valerie (Frontiers in Psychology, 2022)
The future of work is forcing the world to adjust to a new paradigm of working. New skills will be required to create and adopt new technology and working methods, and cognitive skills, particularly creative problem-solving will be highly sought after. The future of work paradigm has threatened many occupations but bolstered others such as engineering. Engineers must keep up to date with the technological and cognitive demands brought on by the future of work. Using an exploratory mixed-methods approach, our study sought to make sense of how engineers understand and use creative problem solving. We found significant associations between engineers’ implicit knowledge of creativity, exemplified creative problem solving, and the perceived value of creativity. We considered that the work environment is a potential facilitator of creative problem-solving. We used an innovative exceptional cases analysis and found that the highest functioning engineers in terms of knowledge, skills, and perceived value of creativity, also reported working in places that facilitate psychosocially safe environments to support creativity. We propose a new theoretical framework for a creative environment by integrating the Four Ps (Person, Process, Product, and Press) and psychosocial safety climate theory that management could apply to facilitate creative problem solving. Through the acquisition of knowledge to engage in creative problem solving as individuals or a team, a perception of value must be present to enforce the benefit of creativity to the engineering role. The future of work paradigm requires that organisations provide an environment, a psychosocially safe climate, for engineers to grow and hone their sought-after skills that artificial technologies cannot currently replace.